EXAMINING THE RELATIONSHIP BETWEEN LEADERSHIP ORIENTATIONS AND SOCIAL INTELLIGENCE LEVELS OF SPORTS MANAGER CANDIDATES: THE CASE OF SAKARYA - Alemdar, Uğur; Cömert, Esra; Ünlü, Yılmaz; Solakumur, Adem (My University, 2023)
The present research is conducted to determine the effect of social intelligence levels of sports manager candidates on their leadership orientations. In this context, the model of the research is determined as the causal screening model. The sample group of the research consists of 261 students studying at Sakarya University of Applied Sciences Faculty of Sport Sciences. The research data are collected by the Personal Information Form developed by the researcher, the Leadership Orientation Scale developed by Bolman and Deal (1991) and adapted into Turkish by Dereli (2003), and Tromso Social Intelligence Scale developed by Silvera, Martinussen and Dahl (2001), and adapted into Turkish Doğan and Çetin (2009). In the analysis of the collected data; Regression analysis is conducted to determine the effect of social intelligence on leadership orientations. As a result of the research, it has been determined that the social intelligence levels of the sports manager candidates are a positive and statistically significant predictor of their leadership orientation.
Keywords: Spor Bilimleri; Interaction; Sports management; leadership orientation; social ıntelligence